The Characteristics of Property Offenders in Canton Sarajevo (Kriminalističke teme, 2017)
Reason(s) for writing and research problem(s): Research in Bosnia and Herzegovina, especially in Sarajevo Canton, on characteristics of offenders in the field of property crime are rare. There are some research efforts dealing with the extent of property crime, but social and psychological characteristics of offenders are only scarcely investigated. The paper discusses some commonly investigated characteristics of offenders: age at first trouble with the law, family and marital status and relations, school, finances, accommodation, leisure, alcohol and drugs consumption.Aims of the paper (scientific and/or social): The paper aims to describe and discuss characteristics of first time and repeat property offenders, and furthermore, to test the significance of differences. The results could be utilized in treatment design and more appropriate distribution of correctional resources.  Methodology/Design: Research is exploratory in nature and deals with characteristics of thirty repeat and thirty first time male offenders, sentenced for property offences in Sarajevo Canton (Bosnia and Herzegovina). Research instrument is modified and adjusted from previous research from abroad.Research/paper limitations: Research is limited by small number of respondents, therefore not representative for Sarajevo Canton, or Bosnia and Herzegovina. Results on correlates of delinquency would be more compelling if larger number of respondents and different research design, such as longitudinal or similar, were utilized. Results/Findings:  There are differences between repeat and first time offenders, although not always substantial. The results of the research suggest that recidivist offenders had problems at school, that portion of them had other delinquents in families, that they most likely had delinquent peers, and that they tend to have financial and employment problems. Compared to first time offenders, and especially to non-delinquents, it is less likely for recidivists to be in stable marital relationships. It is likely they begun using drugs in adolescent age, which tended to be a long-lasting pattern in their behaviour.General conclusion: There are differences between recidivist and first time property offenders, which are likely to be a result of unfavourable societal circumstances persistent in lives of recidivists since their adolescence. Research/paper validity: The research is important because it tests, based on empirical data, differences in characteristics of first time and repeat offenders, a topic often researched and discussed in criminological research.